2019
DOI: 10.1038/s41598-019-38729-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased temperatures and elevated CO2 levels reduce the sensitivity of Conyza canadensis and Chenopodium album to glyphosate

Abstract: Herbicides are the most commonly used means of controlling weeds. Recently, there has been growing concern over the potential impacts of global climate change, specifically, increasing temperatures and elevated carbon dioxide (CO2) concentrations, on the sensitivity of weeds to herbicides. Here, glyphosate response of both Conyza canadensis and Chenopodium album was evaluated under different environmental conditions. Reduced glyphosate sensitivity was observed in both species in response to increased temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 34 publications
0
30
1
2
Order By: Relevance
“…which simply reduced the effect of the applied doses of glyphosate . In a recent study, Matzrafi et al reported that glyphosate sensitivity was reduced in Conyza canadensis (L.) Cronquist. and C. album under elevated CO 2 concentrations, increased temperatures, and the combination of both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…which simply reduced the effect of the applied doses of glyphosate . In a recent study, Matzrafi et al reported that glyphosate sensitivity was reduced in Conyza canadensis (L.) Cronquist. and C. album under elevated CO 2 concentrations, increased temperatures, and the combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…and C. album under elevated CO 2 concentrations, increased temperatures, and the combination of both. It was established that glyphosate was translocated quickly from treated leaves to shoot meristems and roots under these conditions, which resulted in decreased sensitivity of the treated tissues and therefore, reduced efficacy of glyphosate . The CO 2 enrichment has also been reported to significantly improve the root growth and biomass accumulation which could promote regrowth of perennial weed species like C. arvense , making their chemical control further difficult .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies provide a reference for these treatments. [26][27][28] The response of weed species was determined to different levels of nitrogen in relation to different climatic conditions. Three (low, medium and high) doses of nitrogen were: (i) 0 kg ha −1 (control); (ii) 60 kg ha −1 ; and (iii) 120 kg ha −1 .…”
Section: Treatmentsmentioning
confidence: 99%
“…Another study on broadleaf weed species also indicated that the control of Chenopodium album L. and Conyza canadensis (L.) Cronquist by glyphosate could be reduced under projected future climatic conditions as both weed species were less sensitive to glyphosate under the higher temperature regime (32/26 • C) compared with the lower temperature regime (18/12 • C) [22]. These authors also suggested that altered glyphosate translocation might be the basis for reduced weed sensitivity at high temperatures.…”
Section: Experiments 1 Effect Of Temperature On Glyphosate Efficacymentioning
confidence: 99%
“…As this weed can grow throughout the year, plants produced from these seeds may also become harder to control during the winter months, especially the GR populations. Therefore, over-reliance on glyphosate for weed control in summer fallows may result in more weed control failures [22], especially for weeds like S. oleraceus, which occur throughout the year. Sonchus oleraceus, considered mainly a winter weed in the past, is now a common weed throughout the year in Australia, especially in the Southeast Australian region, where rainfall is distributed throughout the year.…”
Section: Experiments 1 Effect Of Temperature On Glyphosate Efficacymentioning
confidence: 99%